Efficacy of a Transitional Support Program Among Adolescent Patients With Childhood-Onset Chronic Diseases: A Randomized Controlled Trial - Morisaki-Nakamura, Mayumi; Suzuki, Seigo; Kobayashi, Asuka; Kita, Sachiko; Sato, Iori; Iwasaki, Miwa; Hirata, Yoichiro; Sato, Atsushi; Oka, Akira; Kamibeppu, Kiyoko (Frontiers in Pediatrics, 2022)
It is recommended that patients with childhood-onset chronic diseases (CCD) be transferred from pediatric to adult healthcare systems when they reach adulthood. Transitional support helps adolescents with CCD transition smoothly. Transition readiness is one of the key concepts to assess the efficacy of transitional support programs. This study aims to investigate the effect of a transitional support program on transition readiness, self-esteem, and independent consciousness among Japanese adolescents with various CCD using a randomized controlled trial. Adolescents with CCD aged 12–18 years participated in a randomized controlled trial evaluating the efficacy of a transitional support program. The patients in the intervention group visited transitional support outpatient clinics twice. They answered questionnaires regarding their disease and future perspectives to healthcare professionals and independently made a short summary of their disease. All the participants answered the questionnaires four times. Eighty patients participated in this study. Among those in the intervention group, transition readiness within one, three, and six months after interventions, and self-esteem within one month after interventions were higher than that of the control group. The scores on the “dependence on parents” subscale at six months after interventions, were lower for the intervention group as compared to the control group. This program is expected to help patients transition smoothly from pediatric to adult healthcare systems.